(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
The article is devoted to the organization of experimental work on teaching English works of fiction based on dramatization. The article examines the use of dramatic elements in the process of teaching literature as a method that promotes a deeper and more emotional perception of the text. The influence of dramatization on the development of language skills, critical thinking skills and intercultural communication in students is explored. The article analyzes the results of the experiment, showing that the use of dramatization helps to improve the understanding of works, develop creativity and confidence in the use of language, as well as increase interest in literature in general.